Modeling and performance analysis of the solar photovoltaic cell model using Embedded MATLAB. (March 2015) - Vimalarani, C; Kamaraj, N
This paper presents the modeling and simulation of photovoltaic (PV) modules using the MATLAB/SIMULINK environment. The main objective was to find the nonlinear current-versus-voltage (I–V) and power-versus-voltage (P–V) characteristics curves for solar PV modules Photonix 150W and Photonix 140W and to compare the results with the manufacturer's data sheet. The Embedded MATLAB function finds the best output current and power with respect to voltage characteristics curves for various cell temperature and solar irradiation values for the solar PV model, which includes the effect of the series resistance. Thus, the parallel resistance, which is infinite, can be neglected for simplification. The modeling method and the proposed Embedded MATLAB function are helpful for power electronics designers, who need a trouble-free and user-friendly modeling method for the simulation of solar PV systems. The parameters that compose various PV models have been proposed by many authors. By changing the parameter values, the output current and power with respect to voltage characteristics curves are acquired, and simulation results match the manufacturer's data.